ORGANIZATION OF INDEPENDENT STUDY THROUGH WEB QUEST TECHNOLOGY - Hamdamov Usmon Ergashevich (Western European Studies, 2024)
The following article is devoted to the actual problem of using information and communication technologies in independent educational activities of students studying a foreign language. The article considers the use of the web quest as a form of organizing independent work, which serves to form creative cognitive activity and independence of students, skills of analysis, synthesis and critical evaluation
Keywords: independent work; web quest; foreign language